2011
DOI: 10.2139/ssrn.1804923
|View full text |Cite
|
Sign up to set email alerts
|

Bank Efficiency in Transition Economies: Recent Evidence from South-Eastern Europe

Abstract: This study examines the cost and profit efficiency of banking sectors in six transition countries of SouthEastern Europe over the period 1998-2008. Using the stochastic frontier approach, our analysis reveals that the average cost efficiency of SEE banks is 68.59% and the average profit efficiency is 53.87%. The second-stage regressions on the determinants of bank efficiency further show that foreign banks are associated with higher profit efficiency but moderately lower cost efficiency. Government banks are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 49 publications
5
14
1
1
Order By: Relevance
“…But is it important to note that these are the best data available even though they may be incomplete. Surprisingly, the results here show that the financial crisis in 2007-2008 had a positive impact on profit efficiency for the banks in Central Asia, which is inconsistent with the existing literature (Fang et al, 2011). 7 However, given the Central Asian States are not integrated into the international financial system this is probably picking up some unobserved factor.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…But is it important to note that these are the best data available even though they may be incomplete. Surprisingly, the results here show that the financial crisis in 2007-2008 had a positive impact on profit efficiency for the banks in Central Asia, which is inconsistent with the existing literature (Fang et al, 2011). 7 However, given the Central Asian States are not integrated into the international financial system this is probably picking up some unobserved factor.…”
Section: Resultscontrasting
confidence: 99%
“…The coefficient on the interaction between state ownership and the time trend is positive, indicating that the state owned banks started to catch up with domestic private owned banks and are more profitable in recent years. This supports the results by Fang et al (2011) and, perhaps, the restructuring, modernisation and competition policies of the banking system in the Central Asia over the last two decades have substantially improved the governance of the institutions. Surprisingly, the lagged value of economic growth has a negative impact on profit efficiency.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We found that cost efficiency (Figure ) trended down 2000–2003, increased through 2008 and has fallen again in the years since; for profit efficiency (Figure ), we observe a negative trend since 2007, reaching minimum levels in 2009 and 2013. These results are evidence for the positive effect of European integration on cost efficiency, which has been reported in previous studies (Kosak et al ; Fang et al ; Gallizo et al ,). This positive effect is explained by the reforms that these countries implemented, which supported a more solid institutional framework that protects the legal rights of banks and increased competition after accession to the EU, including via the entry of foreign banks.…”
Section: Resultssupporting
confidence: 86%
“…This result raises questions about policies that are directed to promote bank competition with the objective of reducing the price of financial services and products (Fang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%